Effective Higher Educational Practices - A Survey of Student Engagement (Malaysian Journal of Learning and Instruction, 2005)
The quest for excellence in teaching and learning in higher education is a world- wide concern. Universities and colleges have responded to the challenge for higher quality in instruction by looking closely at the nature of the typical teaching and learning environment. It is concurred that the quality of undergraduate education largely depends on the quality of teaching provided by faculty. This paper reports on a research project that seek to obtain information about the undergraduate educational experience at a university. In particular, the study focuses on the extent to which undergraduate students engage in good educational practices. An instrument is administered to random samples of final year students to identify the level of student engagement and aspects of the undergraduate experience that could he improved. Findings revealed that the students perceived their campus environment as supportive of their academic needs. They also reported adequate levels of academic challenge and participation in enriching experiences. Nevertheless, students reported lower levels of interaction with faculty members and in active and collaborative learning. Results from the study point to the need for institutional improvement efforts in order to transform undergraduate experience into more holistic and engaging learning environments.